“All shadow and silence in it” (3.1.247-48): Reticence in Measure for Measure - Denis Lagae-Devoldere (Sillages Critiques)
Measure for Measure’s notoriously ambivalent ending, particularly with Isabella’s lack of response to the Duke’s twice-repeated marriage proposal, has caused a wealth of critical comments. It seems that most critics have failed to notice that the silence at the close of the play is actually made palpable throughout the course of the dramatic action: the silence(s) surrounding the “open” ending makes manifest what has been hinted at and toyed with. The bed-trick, one of the play’s central episodes – in both senses of its plot-related importance and its significant structural position – may be construed as a powerful marker of the interplay between silence and discourse, redeployed in specific stage terms. Shakespeare’s last comedy may thus be seen as an exploitation and exploration of aposiopesis in all its varied structural, dramatic, linguistic, political or philosophical nuances or “measures.” Measure for Measure, a play about the failure of rhetorical persuasion, turns reticence into emphasis.